Unleashing language skills for better job prospects / Hazwati Hashim - Hashim, Hazwati (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
The English language has become the most-spoken language around the world. Whatever reasons you have for learning English either it is for job promotion, pursuing your study or for any personal reason you have; it is undeniable that you would need the language someday in your life (“The Benefits of Learning English,” 2016). However, many students do not even realize the importance of not only learning the language but also to acquire the language thus to become proficient in it. In realizing the impact of the English language on career opportunities and social activities (A. Jasim, 2021), not many students are aware that they already have the hidden potential of learning and acquiring the language. Some students learn the language just for passing the subject or to meet the faculty’s requirements. They, on the other hand, do not see the benefits of one skill over the other language skills. The students apparently have always thought of the language as a subject and part of the program. In addition to that, there are four language skills that students usually learned since they were in school until graduating from the universities. The language skills range from reading, listening, writing, and speaking. Along the path of knowing and learning the language skills, one student may be good in writing and not on other skills. Some students may not be good in listening, reading, and writing but are fluent in the spoken form. Thus, these create a variety of language learners, and they must see the hidden potential that they have if they are able to acquire even one skill.